2017
DOI: 10.1128/aac.00004-17
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and In Vitro Antifungal Susceptibility of 200 Clinical and Environmental Aspergillus flavus Isolates

Abstract: Aspergillus flavus has been frequently reported as the leading cause of invasive aspergillosis in certain tropical and subtropical countries. Two hundred A. flavus strains originating from clinical and environmental sources and collected between 2008 and 2015 were phylogenetically identified at the species level by analyzing partial ␤-tubulin and calmodulin genes. In vitro antifungal susceptibility testing was performed against antifungals using the European Committee on Antimicrobial Susceptibility Testing (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 51 publications
1
20
1
Order By: Relevance
“…In the present study, all tested azoles showed potent in vitro activity against all A flavus and A oryzae clinical and environmental isolates. This result is consistent with a previous report in which clinical and environmental A flavus isolates were both tested . Unlike A fumigatus , the development of resistance via environmental selection is not currently a concern for A flavus .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, all tested azoles showed potent in vitro activity against all A flavus and A oryzae clinical and environmental isolates. This result is consistent with a previous report in which clinical and environmental A flavus isolates were both tested . Unlike A fumigatus , the development of resistance via environmental selection is not currently a concern for A flavus .…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with a previous report in which clinical and environmental A flavus isolates were both tested. 31 Unlike A fumigatus, the development of resistance via environmental selection is not currently a concern for A flavus. Recently, a surveillance study in Korea used CLSI ECVs to reveal that 14% (7/50) of A flavus clinical isolates belonged to a non-wild-type genus.…”
Section: Discussionmentioning
confidence: 99%
“…In tropical and subtropical countries of the Middle-East, such as Iran, species of Aspergillus section Flavi are reportedly the main aetiological agents of invasive and non-invasive infections. 3,4 The taxonomy of this section is complex and is currently under development. 5 A large number of species in section Flavi are commonly observed plant pathogens producing several mycotoxins.…”
Section: Amongmentioning
confidence: 99%
“…Although in our case the presence of A. caelatus cannot be related to an active infectious process, it is of importance to consider the in vitro antifungal susceptibility pattern of Aspergillus from the section Flavi and their predominant role as pathogens in tropical and subtropical countries (Taghizadeh-Armaki et al, 2017;Hagiwara et al, 2016). Therefore, it is necessary to know the human pathogenic role of each of them and to develop rapid and easy identification techniques and susceptibility tests.…”
Section: Discussionmentioning
confidence: 91%